2012
DOI: 10.1177/205891581200300203
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Light on Embryos and Embryo Culture

Abstract: In oviparous animals, the egg hatches outside of the body and is exposed to light; in some cases throughout the development of the fetus. In mammals, fertilization and the growth of embryos in vivo occurs in the dark but in human IVF, these embryos are exposed to variable light sources and intensities. Light can affect embryonic development in some species via either a direct toxic effect on the embryo, or indirectly via photo-oxidation of components in the media or oil. Although data regarding the effect of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
(50 reference statements)
0
21
0
Order By: Relevance
“…The female reproductive system is able to protect oocytes, sperm cells, and embryos from potential environmental damage, for example, from visible and nonvisible light exposure. During the procedures of assisted reproduction, the gametes, zygotes, and the embryos are subjected to a variable spectrum of light from different sources, including: ambient light, illumination of the safety cabinet, or light emitted from the microscope or the time-lapse imaging cameras [1, 2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The female reproductive system is able to protect oocytes, sperm cells, and embryos from potential environmental damage, for example, from visible and nonvisible light exposure. During the procedures of assisted reproduction, the gametes, zygotes, and the embryos are subjected to a variable spectrum of light from different sources, including: ambient light, illumination of the safety cabinet, or light emitted from the microscope or the time-lapse imaging cameras [1, 2].…”
Section: Introductionmentioning
confidence: 99%
“…Light exerts harmful effects on the physiology of mammalian gametes and zygotes [2, 3]. Previous studies have shown the damaging effect of visible light on oocytes, sperm cells, and embryos [4-7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, stained embryos cannot be used for ET. The OCT system uses near-infrared light (λ: 900 nm), which has low cytotoxicity [24][25][26], and allows non-invasive observations of bovine embryo morphology; therefore, OCT-scanned embryos can be used for ET. We have also used the same OCT system to observe mouse embryos before ET and achieved a normal delivery after ET (Ohbayashi et al, unpublished data).…”
Section: Textmentioning
confidence: 99%
“…When their difference, Ω = ω p − ω s , matches the vibrational frequency, resonant excitation, and in-phase vibration of all the molecules in the focal volume is observed. This boosts the Raman signal by several orders of magnitude, enabling the shortening of the acquisition time from seconds to milliseconds and minimize the light-toxic effects reported in [98]. The two most widely applied CRS techniques are stimulated Raman scattering (SRS) [99] and coherent anti-Stokes Raman scattering (CARS) [100].…”
Section: Crs Microscopymentioning
confidence: 99%